Behavioural and emotional problems in a Guguletu school: a pilot study - Walaza, Nomfundo (Department of Psychology, 2023)
This paper investigates teachers' perceptions of the prevalence of common emotional and behavioural problems in a black primary school in Cape Town. The rationale in undertaking this study is that there is little epidemiological data pertaining to the incidence and types of particular psychiatric disorders in African children. Also, there were concerns from the staff and students of the Child Guidance Clinic of the University of Cape Town that the facilities and services offered at the clinic are only accessible to a small sector of the community. It is thus hoped that the findings from this study would shape direction for future clinical intervention. A selected review of the relevant literature is given. The needs of the teachers are assessed by finding out the prevalence of emotional and behavioural problems, how they manifest and how teachers perceive them. This is geared towards establishing a hierarchy of priorities for common problems. The analysis is divided into two sections; general pattern of problems and teachers' explanation of problems. Findings reveal that although the problems presented by the teachers in this study are similar to those found in developed or First World countries, teachers use different categories from those normally found in basic psychological or psychiatric texts. Categories are based on the teachers' explanations of a particular behaviour.